Depression among first-year medical students in Universitas Udayana in 2016 - Shireen Anusha Gnanadoss Jebakum; Anak Ayu Sri Wahyuni (Intisari Sains Medis, 2020)
Background: Depression is categorized as a mood disorder which causes changes in a person’s activity as well as life perception and could even cause suicides. Medical students are more distressed than the general population.Aim: This research was conducted to determine the degree of depression among 1st year medical students of Universitas Udayana.Method: This is research is using based on descriptive cross sectional study in order to obtain data about the amount of knowledge students about depression in Udayana University from November 2015 – January 2016. 100 sample sizes are needed for this study. The Beck’s Depression Inventory (BDI) questionnaire is also used in this study.Results: Most of the students in the Medical Faculty of Udayana University have a relatively normal feeling of good and bad that happens in life. A smaller number of students have shown to have mild mood disturbances and but does not indicate the presence depression. The majority of students who suffered from depression are 17 years old based on the BDI scoring, which consisted of 4 students.Conclusion: There female students, they who were living alone, and they who were unable to sleep normally, had the higher prevalence of suffering depression.